Primary field experiences: Critical for primary generalist physical education teachers?. (November 2021) - Murphy, Frances; Marron, Susan; Coulter, Maura
Generalist primary teachers teach physical education in many countries, and their preparation has been the subject of attention internationally. While they undertake field experiences as part of their preparation to teach, it is unclear how much of their teaching is focused on physical education. Reflective practice is recognised as a significant element of their preparation (Korthagen, 2014) with a view to improving practice. The focus of this study is on field experiences and reflective practice of a cohort of generalist primary pre-service teachers (PSTs) ( N =25). This study is a qualitative descriptive study. Data analysed were written reflections chosen because they were considered a powerful professional learning tool. The reflections focused on a particular field experience that consisted of teaching physical education supported by their peers and teacher educators. Findings of the study reveal that the PSTs appreciated the learning environment provided by the field experience, characterised by dialogue, support and encouragement. They saw merit, relevancy and meaningfulness in the experience prior to embarking on it, where both anxiety and excitement were highlighted. While their learning focused on lesson planning, resource management and class organisation, they wrote of learning from observing their peers teaching, from co-teaching and from receiving feedback from teacher educators and peers. They identified the potential to build on this experience within their future evaluated experiences. The focus on physical education within a particular field experience is significant in building the confidence and competence of PSTs.